The Effectiveness of Rheumatic Gymnastics on Patella Joint Flexibility in Elderly with Rheumatoid Arthritis at the Elderly Integrated Service Post (Posyandu Lansia) in Mipiran Village, Purbalingga - Candra Aprian Dwika Prasetyo; Mustiah Yulistiani (Proceedings Series on Health & Medical Sciences, 2024)
Background: Based on data from the 2018 Riskesdas, 7.30% of the Indonesian population is estimated to suffer from rheumatoid arthritis. Rheumatoid arthritis (RA) is a chronic disease that causes joint pain, swelling, stiffness, and limited joint movement. As the most common autoimmune rheumatic disease, rheumatoid arthritis is a chronic inflammatory condition that permanently damages the joints, where the body's immune system, which generally protects the body from infections and diseases, attacks joint tissues for unknown reasons. Method: The research design used in this study was the Pre-Experimental one-group pre-test post-test method. The sample consisted of 31 individuals selected using a total sampling technique. The research instruments used were rheumatic gymnastics SOP and the Long-arm universal goniometer (UG) for measuring patella joint flexibility. Data were analyzed using the Wilcoxon statistical test. Results: There was an increase in the average value of right and left patella joint flexibility before and after the application of rheumatic gymnastics. The obtained P value was 0.005 for the right patella and 0.001 for the left patella. Both statistical analyses discovered that P-value was less than 0.05. Conclusion: Rheumatic gymnastics significantly affects patella joint flexibility in elderly patients with rheumatoid arthritis at the elderly integrated service post (Posyandu Lansia) in Mipiran Village, Purbalingga.